Writing on the Wall : Graffiti and the Forgotten Jews of Late Antiquity - Stern, Karen B. (Princeton University Press, 2018)
Cover -- Title -- Copyright -- Dedication -- CONTENTS -- Illustrations -- Preface -- Acknowledgments -- Abbreviations -- INTRODUCTION Graffiti, Ancient and Modern -- CHAPTER 1 Carving Graffiti as Devotion -- CHAPTER 2 Mortuary Graffiti in the Roman East -- CHAPTER 3 Making One's Mark in a Pagan and Christian World -- CHAPTER 4 Rethinking Modern Graffiti through Ancient -- Notes -- References -- Index.